2014
DOI: 10.1111/icad.12073
|View full text |Cite
|
Sign up to set email alerts
|

Altitudinal trends in species richness and diversity of Mesoamerican parasitoid wasps (Hymenoptera: Ichneumonidae)

Abstract: Utilising short‐term but geographically extensive sampling in Guatemala, Honduras, and Nicaragua, we examined altitudinal trends in species richness and diversity of ichneumonid parasitoid wasps. This study covered 19 subfamilies, including four globally large subfamilies that have not yet been taxonomically revised in the Neotropics. Sampling was done at 25 sites classified into three elevational categories on the basis of the average elevation of traps at each site (low 34–659 m a.s.l., middle 1033–1709 m a.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 31 publications
2
24
0
Order By: Relevance
“…Our results also reinforce conclusions based on studies that examined only selected arthropod taxa. For examples, short‐term Malaise trap studies were found to reliably monitor dipteran communities along Norwegian streams (Diserud, Stur, & Aagaard, ) and to reveal diversity patterns in Mesoamerican ichneumonid faunas that corresponded with well‐documented trends (Veijalainen et al., ). However, a major increase in sampling effort will be needed to comprehensively document biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…Our results also reinforce conclusions based on studies that examined only selected arthropod taxa. For examples, short‐term Malaise trap studies were found to reliably monitor dipteran communities along Norwegian streams (Diserud, Stur, & Aagaard, ) and to reveal diversity patterns in Mesoamerican ichneumonid faunas that corresponded with well‐documented trends (Veijalainen et al., ). However, a major increase in sampling effort will be needed to comprehensively document biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…This pattern is only known for four other groups of insects: the ichneumonids of Central America and Africa (van Noort , Veijalainen et al . ), some ants of the Spring Mountains in the USA (Sanders et al . ), the geometrid moths of the subfamily Larentiinae in the Andean mountains (Brehm & Fiedler , Brehm et al .…”
Section: Discussionmentioning
confidence: 99%
“…To check if this assumption would hold true in ichneumonid data, we tested the relationship between subfamily abundance and species richness within the subfamily using combined data from four datasets where species (or morphospecies) identifications were completed for all subfamilies. This included one dataset from northern Alberta (Finnamore, ), two from the United Kingdom (Owen et al ., ) and one from Central America (Veijalainen et al ., ). To the best of our knowledge, these datasets are the only examples of published studies where species richness numbers were provided for all ichneumonid subfamilies.…”
Section: Methodsmentioning
confidence: 97%